Alleviating impacts of climate change on fishing communities using weather information to improve fishers’ resilience - Okeke-Ogbuafor, Nwamaka; Taylor, Andrea; Dougill, Andrew; Stead, Selina; Gray, Tim (Frontiers in Environmental Science, 2022)
This paper contributes new knowledge in evaluating actions aimed at alleviating impacts of climate change on small-scale fishers and enhancing resilience in their households in West Africa. Evidence of the damage at a community scale, caused by climate change to the artisanal fisheries sector in West African countries, is accumulating. Current measures in place for artisanal fishers to adapt to these changes include broad long-term pro-poor strategies designed to manage the persistent problem of overfishing and declining fish stocks. However, one immediate coping strategy is beginning to emerge – the more active use of reliable weather information. Based on eighty semi-structured interviews conducted in Senegal, Ghana, and Nigeria between 2021 and 2022, this study investigates claims that the use of weather information (WI) is helping West African artisanal fishers and those involved in secondary fisheries activities to build more climate-resilient household income and food security. Unlike the long-term measures for mitigating the impact of climate change, results from the study show that by risk assessing their coastal marine capture activities using weather information, fishers are immediately benefitting. Using the diffusion of innovation theory to investigate the pattern of fishers’ adoption and usage of weather information, we found that Senegalese coastal fishers can be classified as ‘Early Adopters’ of this innovation. However, this is not the case with inland fishers who remain sceptical and will only use weather information if they can ascertain its reliability. West Africa’s inland fisheries sector is often neglected in its national strategies. There is a lack of co-ordinated action to understand the weather information needs of these vulnerable fishers in order to co-assess and co-develop bespoke weather products that offer benefits to them. West Africa’s fisheries, especially those inlands are too important to ignore if the United Nations Sustainable Development Goals including no poverty and zero hunger are to be achieved. To help this sector fully benefit from the use of weather information, this study recommends detailed research into the weather information needs of these fishers and importantly identify targeted-user friendly ways to engage fishers and trust the information.